2018
DOI: 10.1002/lary.27500
|View full text |Cite
|
Sign up to set email alerts
|

Mortality associated with tracheostomy complications in the United States: 2007–2016

Abstract: Objectives/Hypothesis To investigate patterns of tracheostomy‐associated death in the United States. Study Design Retrospective database review. Methods We used Multiple Cause‐of‐Death data from the Centers for Disease Control and Prevention to determine cumulative national mortality associated with tracheostomy complications in the United States from 2007 to 2016. Using International Classification of Diseases, Tenth Revision data, we investigated how frequently tracheostomy‐related complications were reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 25 publications
0
43
0
2
Order By: Relevance
“…2 Uninformed clinicians may attempt to bag mask or orally intubate patients with laryngectomy stomas, potentially causing preventable harm. While tracheostomy-related mortality is well studied, 3 there are minimal data on the oral intubation of patients with a laryngectomy.…”
mentioning
confidence: 99%
“…2 Uninformed clinicians may attempt to bag mask or orally intubate patients with laryngectomy stomas, potentially causing preventable harm. While tracheostomy-related mortality is well studied, 3 there are minimal data on the oral intubation of patients with a laryngectomy.…”
mentioning
confidence: 99%
“…In contrast, black patients in our cohort did not have a higher 30‐day mortality rate despite having overall higher CCI. The discrepancy in mortality rates between black and Hispanic patients contrasts to trends seen in the literature, where black and Hispanic patients often track together in terms of outcomes 19 . Other factors that affect Hispanic‐identifying patients may be at play.…”
Section: Discussionmentioning
confidence: 79%
“…1 From this data, the incorrect conclusion could be drawn that tracheostomy-related deaths are very rare events. The authors identified 623 tracheostomy-related deaths of 25,587,306 total deaths reported and recommended further studies.…”
mentioning
confidence: 95%